KOMPENSASI DAN PENGHARGAAN DALAM MANAJEMEN SUMBER DAYA MANUSIA - Mahmud; Abdul Kholik; Muchamad Ilham Fitrianto (Dar El-Falah, 2023)
Some reasons why compensation is so important: employee motivation,employee retention, competitiveness in the labor market, achievement andproductivity, fairness and employee satisfaction, company culture, costsavings, company reputation. In general, the objectives of compensationmanagement are: cooperative ties, job satisfaction, effective employeeprocurement, motivation, increased productivity, employee stability,discipline, influence of labor unions, influence of the government. Thecommonly applied compensation payment systems are: time system, resultssystem, and piece rate system. The amount of compensation must bedetermined based on job analysis, job description, job specifications, position,external consistency, and guided by justice and labor law. The differencebetween appreciation and recognition lies in its form and intensity. Awardsare a more formal form of recognition and usually involve a physical gift orsome type of award. Recognition, however, is more about providing verbal ornon-monetary appreciation to employees without the need for an associatedphysical gift. Factors that influence the amount of compensation are: supplyand demand for labor, ability and availability of companies, labor unions,employee work productivity, government with laws and presidential decrees,cost of living, employee position, employee education and experience,economic conditions national level, type and nature of work, company's abilityto pay.